The Relationship between Resilience and Psychological Well-Being in New Students Migrating at 'Aisyiyah University Yogyakarta - Zakia Ahnaf Hanifa (Publikasi Indonesia, 2024)
New students who migrate outside their home areas often face adaptation challenges, both academically and socially. This creates emotional distress that can affect their psychological well-being. Resilience, or a person's ability to bounce back from pressure, is considered to play an important role in maintaining the psychological balance of regional students. This study aims to examine the relationship between resilience and psychological well-being in new students who migrate to the University of 'Aisyiyah Yogyakarta. This study uses a quantitative method with a correlational approach. The sample of this study is 97 new students of the 2022-2023 batch taken using a simple random sampling technique. Data were collected through questionnaires that measured the level of resilience and psychological well-being, then analyzed using the Spearman correlation test. The results showed that there was a strong and significant positive relationship between resilience and psychological well-being of overseas students. The high level of resilience in migrant students has been proven to correlate with improved psychological well-being. Resilience plays a significant role in maintaining the psychological well-being of new students who travel. Therefore, it is important for educational institutions to provide support that helps students develop resilience to face challenges during their studies.